2023
DOI: 10.1038/s41598-023-43613-w
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of graphene oxide-doped silica aerogel using supercritical method for efficient removal of emerging pollutants from wastewater

Subhash Kumar Sharma,
P. Ranjani,
Hadas Mamane
et al.

Abstract: Emerging pollutants and a large volume of unused dyes from the textile industry have been contaminating water bodies. This work introduces a scalable approach to purifying water by the adsorption of Acid green 25 (AG), Crystal Violet (CV), and Sulfamethoxazole (SMA) from an aqueous solution by graphene oxide (GO) doped modified silica aerogel (GO-SA) with supercritical fluid deposition (SFD) method. Characterization of GO-SA using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), high-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…The doping of GO in silica aerogel was done in a customized high vacuum using a supercritical method. 3 The emerging contaminant removal studies were performed in 100 mL of solution, as demonstrated in Fig. 2a.…”
Section: Recent Trends In Biomass-based Graphene Aerogelsmentioning
confidence: 99%
See 4 more Smart Citations
“…The doping of GO in silica aerogel was done in a customized high vacuum using a supercritical method. 3 The emerging contaminant removal studies were performed in 100 mL of solution, as demonstrated in Fig. 2a.…”
Section: Recent Trends In Biomass-based Graphene Aerogelsmentioning
confidence: 99%
“…2d. 3 Shukla et al reported efficient adsorptive removal of histamine from red wine using a crude biomass derived graphene aerogel. The designed setup could contain a contaminated liquid sample and the flow rate of liquid can be regulated by N 2 pressure.…”
Section: Recent Trends In Biomass-based Graphene Aerogelsmentioning
confidence: 99%
See 3 more Smart Citations